THE ANALYSIS OF SPEECH ACT IN VERBAL COMMUNICATION BETWEEN HEALTHCARE PROFESSIONALS AND PATIENTS IN PUBLIC HEALTH CENTRE BRANCH KEROBOKAN KELOD - Ni Komang Purwaningsih; Si Putu Agung Ayu Pertiwi Dewi (Journal of English Educational Study (JEES), 2019)
Language plays an important role in our life. Through language, we can transmit messages, communicate ideas, thoughts, and opinions. It is realized that language as the main tool for communication. In everyday communication, we are attuned not primary to the sentences we utter to one another, but also the speech act of those utterances. Communication will be successful when there is no misinterpretation. Communication can be held based on the situations, means that different speech situations will show the use of different speech acts too. One of the speech situations which can give us an idea of the usage of speech acts is in the health care sector. This study aimed at analyzing speech act in verbal communication between healthcare professionals and patients in Public Health Centre Branch Kerobokan Kelod.This study used the descriptive qualitative method with a total sampling technique. The population and sample of this study were the entire healthcare professional in Public Health Centre. The number of samples was 25 respondents.This study is expected to improve the healthcare professional’s skill in communicating based on the situation, therefore, the goal of health service which is targeted can be reached by the patients or patients’ family.